The The Impact of Preceptorship Programs on Stress Levels Among Newly Graduated Nurses - Yessy Winda Aziz; Rachmawaty M.Noer; Mira Agusthia (Nursing Current: Jurnal Keperawatan, 2026)
The transition period from academic education to clinical practice often exposes newly graduated nurses to high levels of stress due to increased responsibilities and workplace demands. This study aimed to examine the impact of preceptorship programs on stress levels among newly graduated nurses at Awal Bros Hospital Pekanbaru. This study employed a quantitative analytic design with a cross-sectional approach. All newly graduated nurses who had worked for three months or less at Awal Bros Hospital Pekanbaru during the study period were invited to participate. Using a total sampling technique, 37 eligible nurses were recruited and included in the study. Data were collected using a preceptorship program questionnaire and the Expanded Nursing Stress Scale (ENSS) and were analyzed using the Chi-square test. The results showed that 59.5% of the preceptorship programs were categorized as less appropriate, and 56.8% of nurses experienced stress. Statistical analysis revealed a significant relationship between preceptorship programs and stress levels (p = 0.001; OR = 18.000). These findings indicate that suboptimal preceptorship programs significantly increase the risk of stress among newly graduated nurses. Strengthening structured preceptorship programs is recommended to support adaptation and reduce stress levels.